Melittin, a Potential Natural Toxin of Crude Bee Venom: Probable Future Arsenal in the Treatment of Diabetes Mellitus - Hossen, Md. Sakib; Siew, Hua Gan; Khalil, Md. Ibrahim (Hindawi Publishing Corporation, 2017)
Since diabetes mellitus (DM) is one of the most common and serious endocrine metabolic disorders, it is important to elucidate novel antidiabetic therapeutic agents from various sources, including natural products. Bee venom (BV) is a complex mixture of proteins, peptides, and low molecular components, and melittin is the main constituent. Melittin is a peptide consisting of 26 amino acids with the sequence GIGAVLKVLTTGLPALISWIKRKRQQ. It has several important biological effects and has a relatively low toxicity. Recent studies using animal models have confirmed that melittin has significant glucose and lipid lowering activities by acting on several mechanistic pathways. The main antidiabetic activity of melittin is increasing insulin secretion via depolarization of pancreatic